Tidal impacts on air-sea CO2 exchange on the North-West European shelf - Kossack, Jan; Mathis, Moritz; Daewel, Ute; Liu, Feifei; Demir, Kubilay Timur; Thomas, Helmuth; Schrum, Corinna (Frontiers in Marine Science, 2024)
Tidal forcing is a dominant physical forcing mechanism on the Northwest European Shelf (NWES) that regulates the mixing-stratification status of the water column and thus acts as a major control for biological productivity and air-sea CO2 exchange. Tides further influence the marine carbon cycle on the shelf by affecting benthic-pelagic coupling, vertical mixing and the large-scale residual circulation. The cumulative tidal impact on oceanic uptake of atmospheric CO2 on the NWES, however, remains largely unexplored. We use a coupled physical-biogeochemical ocean model to gain quantitative understanding of the tidal impacts on the air-sea CO2 exchange of the NWES by comparing hindcast simulations with and without tidal forcing. Our results show that tidal forcing weakens the annual oceanic CO2 uptake on the NWES by 0.15 Tmol C yr−1, corresponding to a ~13% stronger CO2 sink in the experiment without tidal forcing. The tide-induced increase in marine primary production demonstrated in earlier studies, which primarily enhances biological carbon fixation in shallow inner-shelf regions of the NWES, does not significantly affect net air-sea CO2 exchange. Instead, we find tidal mixing, tide-induced baroclinic circulation and the tidal impact on benthic-pelagic coupling to be dominant controls of air-sea CO2 exchange. Tidal mixing in the permanently mixed shelf regions accounts for the majority (~40%) of the weakening effect on CO2 uptake, while the modulation of water mass composition in the Celtic Sea by tide-induced baroclinic circulation reduces the uptake further (~33% of the difference in annual mean CO2 uptake). In terms of the shelf carbon budget, the tidal response of air-sea CO2 exchange is primarily mediated by changes to the pelagic DIC reservoir (~73%; −0.11 Tmol C yr−1). Tidal impacts on off-shelf carbon export to the North Atlantic only account for ~20% (−0.03 Tmol C yr−1) of the tidal impact on shelf CO2 uptake, and changes in sedimentation of particulate organic carbon account for the remaining ~7% (−0.01 Tmol C yr−1).